Complementary traditional Chinese medicine therapy improves survival in patients with metastatic prostate cancer. Issue 31 (August 2016) - Liu, Jui-Ming; Lin, Po-Hung; Hsu, Ren-Jun; Chang, Ying-Hsu; Cheng, Kuan-Chen; Pang, See-Tong; Lin, Shun-Ku
Abstract : Abstract: More than 50% of prostate cancer patients have used traditional Chinese medicine (TCM) in Taiwan. However, the long-term clinical efficacy of TCM in prostate cancer patients remains unclear. Here, we investigated the relationship between TCM use and the survival of prostate cancer patients. A retrospective nationwide cohort study of prostate cancer patients was conducted between 1998 and 2003 using the Taiwan National Health Insurance Research Database. Patients were classified as TCM users or nonusers, and monitored from the day of prostate cancer diagnosis to death or end of 2012. The association between death risk and TCM use was determined using Cox proportional-hazards models and Kaplan–Meier curves. Of the 1132 selected prostate cancer patients, 730 (64.5%) and 402 (35.5%) were TCM users and nonusers, respectively. The mean follow-up period was 8.38 years, and 292 (25.8%) deaths were reported. TCM users had a decreased mortality rate (21.9%) compared with nonusers (32.8%). A lower death risk was observed with longer TCM use, especially in patients who used TCM for ≧200 days (adjusted hazard ratio [aHR] 0.61, 95% confidence interval [CI] 0.44–0.84). TCM users with metastatic prostate cancer had a significant lower HR than nonusers (aHR 0.70, 95% CI 0.51–0.95). Chai-Hu-Jia-Long-Gu-Mu-Li-Tang was the most significant TCM formulae for improving survival in metastatic prostate cancer (aHR 0.18, 95% CI 0.04–0.94). The result suggested that complementary TCM therapy might be associated with a reduced risk of death in metastatic prostate cancer patients. Abstract : Supplemental Digital Content is available in the text